Inguinal endometriosis: A systematic review - Alexandros Dalkalitsis; Styliani Salta; Ioannis Tsakiridis; Themistoklis Dagklis; Ioannis Kalogiannidis; Apostolos Mamopoulos; Angelos Daniilidis; Apostolos Athanasiadis; Iordanis Navrozoglou; Minas Paschopoulos; Anastasia Vatopoulou; Ioannis Kosmas (Elsevier, 2022)
Inguinal endometriosis is a very rare entity with uncertain pathophysiology, that poses several diagnostic and therapeutic challenges. This study aimed to summarize published literature on the diagnosis and treatment of this condition. Thus, a systematic literature search was conducted in PubMed/MEDLINE, Scopus and the Cochrane Library. An effort was made to numerically analyze all parameters included in case reports and retrospective analyses, as well. The typical and atypical features of this condition, investigations used, type of treatment and histopathology were recorded. More specifications about the surgical treatment, such as operations previously performed, type of surgery and treatment after surgery have been acknowledged. Other sites of endometriosis, the presence of pelvic endometriosis and the follow-up and recurrence have been also documented. Overall, the search yielded 61 eligible studies including 133 cases of inguinal endometriosis. The typical clinical presentation includes a unilateral inguinal mass, with or without catamenial pain. Transabdominal or transvaginal ultrasound was typically used as the first line method of diagnosis. Groin incision and exploratory surgery was the treatment indicated by the majority of the authors, while excision of part of the round ligament was reported in about half of the cases. Chemotherapy and radiotherapy were initiated in cases of coexisting endometriosis-related neoplasia. Inguinal recurrence or malignant transformation was rarely reported. The treatment of inguinal endometriosis is surgical and a long-term follow-up is needed. More research is needed on the effectiveness of suppressive hormonal therapy, recurrence rate and its relationship with endometriosis-associated malignancies.